Is there a market for multi-peril crop insurance in developing countries moving beyond subsidies? Evidence from India - Ghosh, Ranjan Kumar; Gupta, Shweta; Singh, Vartika; Ward, Patrick S. (International Food Policy Research Institute, 2019)
Researchers and policymakers have long understood the benefits of crop insurance but have been consistently disappointed by the poor performance of these programs. Rarely have programs seen sizeable take-up rates without support through large government subsidies, and in many countries, demand has been meager even at prices well below fair-market rates. Experiences from India have largely followed this trend, despite a number of large policy initiatives. Limited demand stems from low perceived value, arguably because the existing insurance products are unsuited to farmers’ needs. The present study fills an important gap in rural development by improving upon existing insurance policy design by incorporating product characteristics better suited to farmers’ preferences. To do so, we conducted a discrete choice experiment with agricultural households in four states in India. While farmers seem to like several of the features of policies offered under existing programs, our results suggest they would generally be willing to pay more than the highly subsidized rate they currently pay and are also clearly dissatisfied with delayed and uncertain indemnity payments and would be willing to pay a significant premium for more assured and timely payment delivery.